2009
DOI: 10.1289/ehp.0800194
|View full text |Cite
|
Sign up to set email alerts
|

Air Pollution Exposures and Circulating Biomarkers of Effect in a Susceptible Population: Clues to Potential Causal Component mixtures and mechanisms

Abstract: BackgroundMechanisms involving oxidative stress and inflammation have been proposed to explain associations of ambient air pollution with cardiovascular morbidity and mortality. Experimental evidence suggests that organic components and ultrafine particles (UFP) are important.MethodsWe conducted a panel study of 60 elderly subjects with coronary artery disease living in retirement communities within the Los Angeles, California, air basin. Weekly biomarkers of inflammation included plasma interleukin-6, tumor n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
188
3
6

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 270 publications
(222 citation statements)
references
References 37 publications
25
188
3
6
Order By: Relevance
“…Monitors inside and outside homes of retirees (Delfino et al, 2008(Delfino et al, , 2009. Mobile monitors that travelled with retirees (Adar et al, 2007).…”
Section: Casac and Nrc Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Monitors inside and outside homes of retirees (Delfino et al, 2008(Delfino et al, , 2009. Mobile monitors that travelled with retirees (Adar et al, 2007).…”
Section: Casac and Nrc Considerationsmentioning
confidence: 99%
“…All of these biological changes are factors in development of cardiovascular diseases. Delfino et al (2008Delfino et al ( , 2009 found elevated platelet P-selectin expression and depletion of erythrocyte superoxide dismutase (SOD) in a panel study of elderly residents of retirement centers in Los Angeles, in association with higher concentrations of BC, EC, and primary organic carbon (POC), suggesting commonality of effects from different sources of similar emissions. Increased ROS has been found in association with exposure to diesel emissions in workplaces (e.g., Sauvain et al, 2009, bus maintenance workers; Lee et al, 2011, diesel exhaust inspectors).…”
Section: Overview Of Health Effectsmentioning
confidence: 99%
“…It has been reported that exposure to particulate air pollution causes a decrease in erythrocyte antioxidant enzyme activity [8]. A decrease in erythrocytes in association with exposure to either particulate air pollution or nanoparticles in humans and experimental animals has been reported [9,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Air pollution has been linked to a variety of health outcomes, but the strongest evidence for pathways from exposure to disease exists for traffic-related air pollution and cardiovascular disease (Rosenlund, Berglind, Pershagen, Hallqvist, Jonson and Bellander, 2006; Tonne, Melly, Mittleman, Coull, Goldberg and Schwartz, 2007), all cause mortality (Jerrett, et al, 2009a; Jerrett, et al, 2009b), and asthma exacerbations (Kunzli, et al, 2000). Recently, exposure to PAHs, which are a major component of primary traffic emissions (HEI Panel on the Health Effects of Traffic-Related Air Pollution 2010), has been associated with relevant biomarkers (Delfino, et al, 2009) and implicated as a contributor to the onset of asthma (Burton, 2009; McConnell, et al, 2010). …”
Section: Introductionmentioning
confidence: 99%